Program Nasional Pemberdayaan Masyarakat (PNPM) in Indonesia: The Challenge of Governance - Anggun Trisnanto Hari Susilo (Jurnal Transformasi Global, 2015)
AbstractÂ Poverty is an issue that has been discussed seriously in international development. Donors, bilateral and multilateral now are pushing forward series of efforts to address this issue. Among others, governance is one of the prominent efforts to tackle poverty. Notably, governance is a complex system, which requires components to support. Democracy, decentralization, rule of law and active people participation are few. In fact, there are limited resources academically and empirically on how these components interacting. Taken from current research on Community-Driven Development (CDD) program in Indonesia named Program Nasional Pemberdayaan Masyarakat (PNPM) or National Program for Community Empowerment- a project that initially promoted by the World Bank, this paper argues that such components in governance are conflicting one and another. More, rather than reducing poverty, promoting governance in CDD leads to the path of uncertainty which ends with two major consequences namely creation of potential conflict and sustainability of elite capture. Disorganized mechanism between decentralization and local democracy brings to the former consequences while uncoordinated system between PNPM and regular Indonesian development planning causes the latter. The first consequence is found in sub-district level, whereas the second is taken from local/ village level. The research applies qualitative methodology in which semi ethnographic approach; close observation and in-depth interviews are the central techniques. To add, this paper will be structured into three parts. Literature review on governance, decentralization and participation is presented in the first section followed by implementation of PNPM in the second. Third section will discuss findings and ends with a conclusion.Â Keywords; Governance, PNPM, and decentralization